Fatigue Indices and Perceived Exertion Highlight Ergometer Specificity for Repeated Sprint Ability Testing - Kerhervé, Hugo A.; Stewart, David G.; McLellan, Chris; Lovell, Dale (Frontiers in Sports and Active Living, 2020)
This study aimed to compare the timecourse of measures of performance, fatigue and perceived exertion during repeated-sprint ability (RSA) testing performed on non-motorised treadmill (NMT) and cycling ergometer (CE). Fourteen physically-active participants performed two 10x6s RSA tests with a 1:4 work-to-rest ratio (24 s recovery) on NMT and CE. Measures of performance (peak power output [PPO] and the time to reach PPO [TTP]), of fatigue (fatigue index and performance decrement score) and ratings of perceived exertion (RPE) were collected during each session. The level of significance was set at p<0.05. Participants’ weight was significantly correlated with PPO on CE only, and PPO on CE and NMT were significantly correlated only for absolute measures of power. TTP was significantly shorter and more affected by fatigue on NMT than on CE. Fatigue indices were significantly greater on NMT compared to CE, with significant positive correlations between fatigue and absolute and relative PPO on both ergometers. During RSA, RPE increased more on NMT compared to CE from bouts 3 to 7. During recovery, RPE was consistently higher on NMT at 1, 3 and 5 min postexercise compared to CE. These findings indicate that RSA performed on NMT induces greater fatigue and physiological load than CE, which could originate in fundamental differences in active muscle mass and power application patterns between running and cycling. These findings underscore ergometer specificity for RSA testing and provide further insights for sport scientists and coaches to evaluate ergometer specificity requirements for testing and exercise prescription and programming.